Identification of a new type tadalafil analogue in a supplement product. Issue 7 (3rd July 2018) - Huang, Yen-Chun; Lee, Hui-Chun; Lin, Yun-Lian; Tsai, Chia-Fen; Cheng, Hwei-Fang
ABSTRACT: A novel compound structurally similar to tadalafil was found in a dietary supplement by adulterants screening test and isolated by column chromatography. After analysis by accurate mass, nuclear magnetic resonance (NMR) and X-ray, the structure of this novel tadalafil analogue was determined as (5 R, 16 R )-5-(1, 3-benzodioxol-5-yl)-2- (3-ethypentan-3-yl)-15, 16-dihydro(1 H -imidazo[1, 5- a ]pyrido)[3, 4- b ]indol-1, 3-dion GRAPHICAL ABSTRACT: